Determination of the influence of certain industrial capacities to the environment - Anovski, Todor (Macedonian Journal of Ecology and Environment, 1997)
Necessity of parallel care for both, permanent technological development and improvement or conservation of the local environment is discussed. Through own and investigations performed in other' countries, registered influences of individual industrial capacity to the environment with special attention to the surface and underground waters most oftenly used in local water supply, are shown.